2019
DOI: 10.3991/ijep.v9i2.9950
|View full text |Cite
|
Sign up to set email alerts
|

Mixing Educational Robotics, Tangibles and Mixed Reality Environments for the Interdisciplinary Learning of Geography and History

Abstract: In the present study we present a mixed reality learning environment that aims to become a creative, joyful and efficient interdisciplinary canvas for learning about history and geography and for concurrently fostering computational thinking. The environment makes use of embodied affordances and educational robotics and consists of two parts: an augmented 3D-tangible model of southern Europe with finger-based interaction and a second floor-based augmented robotics track de-picting European landmarks, where stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Previous research has used various platforms to provide teachers immersive training experiences, such as TeachLivE™ (e.g., Dieker et al, 2019; Fraser et al, 2020), Mursion (e.g., Gundel et al, 2019; Gundel & Piro, 2021), and Unity 3D (e.g., Huo et al, 2021; Stavroulia & Lanitis, 2020), which demonstrated great potential of VR in teacher education. In such VR environments, teachers were trained in professional competencies in areas such as classroom management (e.g., Chen, 2022; Cohen et al, 2020) and professional noticing (e.g., Ferdig & Kosko, 2020; Huang et al, 2021), domain‐specific knowledge (e.g., Artun et al, 2020; Xefteris & Palaigeorgiou, 2019) and improved their self‐efficacy (e.g., Gundel et al, 2019; Pendergast et al, 2022). Due to the exponential development of VR hardware and software during the last decade, not only VR but also augmented reality (AR) and mixed reality (MR) have been widely utilised in the teacher education area.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research has used various platforms to provide teachers immersive training experiences, such as TeachLivE™ (e.g., Dieker et al, 2019; Fraser et al, 2020), Mursion (e.g., Gundel et al, 2019; Gundel & Piro, 2021), and Unity 3D (e.g., Huo et al, 2021; Stavroulia & Lanitis, 2020), which demonstrated great potential of VR in teacher education. In such VR environments, teachers were trained in professional competencies in areas such as classroom management (e.g., Chen, 2022; Cohen et al, 2020) and professional noticing (e.g., Ferdig & Kosko, 2020; Huang et al, 2021), domain‐specific knowledge (e.g., Artun et al, 2020; Xefteris & Palaigeorgiou, 2019) and improved their self‐efficacy (e.g., Gundel et al, 2019; Pendergast et al, 2022). Due to the exponential development of VR hardware and software during the last decade, not only VR but also augmented reality (AR) and mixed reality (MR) have been widely utilised in the teacher education area.…”
Section: Introductionmentioning
confidence: 99%
“…trained in professional competencies in areas such as classroom management (e.g., Chen, 2022;Cohen et al, 2020) and professional noticing (e.g., Ferdig & Kosko, 2020;Huang et al, 2021), domain-specific knowledge (e.g., Artun et al, 2020;Xefteris & Palaigeorgiou, 2019) and improved their self-efficacy (e.g., Gundel et al, 2019;Pendergast et al, 2022). Due to the exponential development of VR hardware and software during the last decade, not only VR but also augmented reality (AR) and mixed reality (MR) have been widely utilised in the teacher education area.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It is useful and motivating to work in a team on complex tasks close to those solved in a real business environment [5]. Applying knowledge in different areas to solve interdisciplinary tasks inspires learners [6], [7]. They do not like to be bored and look for challenges to demonstrate their abilities to themselves or others.…”
Section: Introductionmentioning
confidence: 99%
“…The course is based on collaborative work, within immersive embodied environments that encourage more than just basic science skills (critical thinking, computational thinking, logic and application of science methodology) but also skills directly related to the arts and humanities such as creativity, imagination ,and reflection on ethical implications [6][7][8]. The course, in addition to educational robotics, integrates multiple ICT tools that support and enrich teaching scenarios, such as Scratch games, Makey-Makey and augmented reality applications [9,10], an embodied learning teaching framework [11,12], and utilizing robots as tools for simulation [13].…”
Section: Introductionmentioning
confidence: 99%